Accelerated Return to Play for Professional Rugby Players After Facial Fractures. Issue 4 (June 2019) - Hada, Shinnosuke; Seto, Hiroaki; Kaketa, Takefumi; Nagayama, Masataka; Kawasaki, Takayuki; Takazawa, Yuji; Tomita, Yoshimasa; Kaneko, Kazuo
Abstract : Background: Facial fractures may result in a significant time away from competition for professional rugby players. An understanding of the return-to-play times is an integral part of clinical decision making when treating professional athletes. A period of 8 to 12 weeks has been conventionally recommended for returning to collision sports after facial fractures. The conventional time to return to sports of 8 to 12 weeks is usually too long for professional players. However, the time of return to play after such facial fractures in elite athletes has not been well described. Purpose: To investigate the return to play after facial fractures in professional rugby players with an accelerated rehabilitation protocol. Methods: Ten professional rugby players with facial fractures were identified and analyzed. The authors investigated the number of days required to return to training and full-contact play according to the trauma type. The authors also determined the presence or absence of refractures and sequelae. Results: The average age of the patients was 26.9 years. Medial orbital wall fractures were the most represented pattern, followed by orbital floor fractures and zygomatic arch fractures. The players returned to jogging after 9.9 days, to sports-specific training after a mean of 10.8 days, and to full-contact training after 18.3 days. There were no cases of refractures and sequelae. Conclusion: Players were able to return to their regular rugby activities, earlier than the time commonly allowed to return to full activity.